Pathological and bacteriological examination ot' pneumonia in beef cattle - İhsan Yaman; Hasan Basn Gülcü (Eurasian Journal of Veterinary Sciences)
In this study, the lungs ot 1216 various breeds of beet cattle aged 6-24 months slaughtered in Elazığ Gunet slaughterhouse were examined macroscopicatly for pneumonia on the dates ot December 2001- February 2002. Pneumonias were determined in the 149 (12.25%) lungs which had been examined Microscopically, pneumonias were classified as tollows: interstitial pneumonia (36 24%), catarrhal-puruleni bronchopneumonia (27.52%), libnnous bronchopneumonia (16.11%), necrotic bronchopneumonia with abscessalion (8.72%l and verminous pneumonia (i 1.41%). In the bacteriological investigation, pure or mix bacteria izolation were made in 32.21% ot pneumonia lungs. There was no bacterial isolation in 67.79% ol pneumonia lungs. As a result of bacterial isolation, S. aureus was the most common microorganism (14.76%), and it followed by Corynebactertum spp. (7 38%)